Enterococcus gallinarum Spontaneous Bacterial Peritonitis in an HCV Cirrhotic. (7th May 2015) - Abidali, Hussein; Sheikh, Maheen; Abidali, Moustapha; Abidali, Ali; Farraji, Hamoudi S.; Berry, Andrew C.
Abstract : We present the case of a 60-year-old Caucasian male with history of hepatitis C viral cirrhosis with portosystemic encephalopathy and ascites with evidence of spontaneous bacterial peritonitis (SBP) with absolute neutrophil count (ANC) of 944 cells/ µ L blood. Despite adequate treatment, the abdominal pain and elevated creatinine continued to persist. Initial ascites fluid cultures returned back positive for growth of Enterococcus gallinarum . Empiric antibiotics were then substituted with ampicillin/sulbactam. Our case of Enterococcus gallinarum causing SBP is only the seventh case reported in the literature to date.